Experimental and theoretical analysis of severely damaged concrete beams strengthened with CFRP. (30th July 2018) - Kabir, Muhammad Ikramul; Subhani, Mahbube; Shrestha, Rijun; Samali, Bijan
Highlights: Repairing of severely damaged reinforced concrete beams with CFRP. Beams fabricated from concrete with fly ash, waste rubber and polypropylene fibres. Theoretical verification of experimental results adopting shear friction model. Reasonable accuracy of theoretical results compared to the experimental results. Abstract: In recent years, carbon fibre reinforced polymer (CFRP) has gained its popularity for repairing reinforced concrete structures. At the same time, numerous research have been conducted on the use of different admixtures in the concrete to enhance its various physical properties. This study investigates the repairing techniques of three concrete beams which contain fly ash, waste rubber and polypropylene fibre in the concrete mix. The control beams were loaded up to its ultimate strength (severely damaged) and then repaired using CFRP, externally bonded to the beam soffit and anchored with complete CFRP wraps. The repaired beams were tested under four-point bending set-up to investigate its failure modes and improvement in strength, stiffness and ductility. In terms of strength and stiffness, two of the repaired beams (with fly ash and waste rubber) exceeded the capacity of the control beams, whereas the beam with polypropylene fibre gained around half of the strength and stiffness compared to its control counterpart. While the ductility of the repaired beams was found to be less than the control ones, the repaired beams exhibit pseudo ductile behaviour. In addition, an analytical study is conducted considering the effect of transverse CFRP anchorage wraps on the flexural capacity of repaired beams using shear friction model which can predict the strength of repaired beam to great accuracy.